CAUSES AND RESULTS OF REOPERATIONS IN OTOSCLEROSIS - Borysenko, O.M.; Sushko, Yu.O.; Srebnyak, I.A.; Mishchanchuk, N.S.; Bezshapochnyi, S.B.; Serbin, G.S. (World of Medicine and Biology, 2019)
The purpose of the work was to study the causes of failures, their frequency and the functional results of reoperations in otosclerosis. A retrospective analysis of 787 stapedoplasty operations results in patients with otosclerosis, which were operated in the period from 2013 to 2017 at AS Kolomiychenko Institute of Otolaryngology NAMS of Ukraine, 43 (5.5%) patients of which were re-operated. In 37 (86%) patients the cause of reoperation was hearing loss, in 6 (14%) - complaints of dizziness, which arose after stapedoplasty, due to the installation of too long a prosthesis. In 12 patients, the cause of the hearing loss after the stapedoplasty was the re-obliteration of the stirrup plate with bone tissue and fixation of the prosthesis; in 2 patients anterior crus of stapes fixing the incus was preserved; in 9 patients there was fixation of the incus and malleus into the attic; in 2 patients the prosthesis fixation with adhesions was observed; in 8 patients displacement of the prosthesis and lack of contact with the incus were reported, in 2 patients there was fixation of the stirrup plate (reancillosis) after its mobilization; in 2 there was intra- cochlear conduction block. Hearing improvement after reoperations was achieved in 91.9% of observations. In 2 cases, no hearing improvement was achieved.